Impact of reducing excess body weight and physical inactivity on cancer incidence in Germany from 2020 to 2050: a simulation model - Gredner, Thomas; Niedermaier, Tobias; Steindorf, Karen; Brenner, Hermann; Mons, Ute (European journal of cancer, 2022)
Background - Excess body weight and physical inactivity are key cancer risk factors contributing substantially to the cancer burden in Germany. We aimed to estimate the numbers and proportions of future cancer cases prevented under different scenarios of reducing the prevalence of excess body weight and physical inactivity in Germany. - Methods - Based on a macro-simulation approach calculating age-, sex-, and cancer-site specific potential impact fractions, we estimated for a 30-year study period (2020-2050) numbers and proportions of cancer cases prevented under different scenarios of reducing excess body weight (overweight and obesity) and increasing levels of physical activity in the German population. - Results - Estimates of the prevented cancer burden varied in the different scenarios. In the guideline exposure scenarios, in which the prevalence of excess body weight and insufficient levels of physical activity would be eliminated, 8.7% (men: 10.1%; women: 7.8%) of overweight/obesity-related cancer cases and 2.4% (men: 2.3%; women: 2.4%) of cancer cases related to physical inactivity were estimated to be prevented over a 30-year period. This translates to approximately 662,000 (men: 304,000; women: 358,000) and 129,000 (men: 42,000; women: 87,000) prevented cancer cases, respectively. - Conclusion - Our results illustrate that a substantial number of future cancer cases could be prevented in the German population by reducing excess body weight and physical inactivity.
Available online 30 November 2021
Gesehen am 24.06.2022